اثر حوكمة الشركات على جودة اداء مراقب الحسابات أنموذج مقترح - النواس, رافد عبيد (Journal of Economics and Administrative Sciences, 2008)
The research aims to:• Show the effect of corporate governance on the quality performance of certified public accountants through establish the concept and principles of corporate governance and the concepts, importance, standards of quality auditing.• Forming a proposed framework for quality performance of certified public accountants under the corporate governance, which show the concepts objectives, principles, standards, and constraints of the proposed framework.The research in one aspect of it based on the study of theoretical background which re which relate to the subject beside the global experiments and opinions of the specialists to frame the proposed framework.At the end of the research we had reached that there is an important need to establish a local central committee take the responsibility of manage and issue the standards and instructions which relate to the subject.